2011
DOI: 10.1007/bf03404903
|View full text |Cite
|
Sign up to set email alerts
|

‘Before You Teach Me, I Cannot Know’: Immigrant Women’s Barriers and Enablers With Regard to Cervical Cancer Screening Among Different Ethnolinguistic Groups in Canada

Abstract: Objective: To describe the similarities and differences among multiple groups of immigrant women and Canadian-born women of low socio-economic status regarding barriers and enablers associated with cervical cancer screening, in order to inform core elements of a strategy that would be acceptable across multiple underscreened groups.Method: Within a health behaviour framework, we used a qualitative explanatory multiple-case study approach consisting of focus group interviews (n=11) in Hamilton, Canada. Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
51
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 15 publications
(19 reference statements)
7
51
1
Order By: Relevance
“…Cultural beliefs and religious practices are a significant part of this community and the impact of religion advocating for healthy life style as well as an emphasis on the role of god and prayer in predicting one's health were clearly identified. Our findings are consistent with other studies that have reported on these views of religion, and modesty in regards to cervical cancer screening [18, 20, 21]. At the system level, our study participants indicated that the health care providers who do not share their similar religious beliefs find it hard to understand why the women decline to screen.…”
Section: Discussionsupporting
confidence: 89%
“…Cultural beliefs and religious practices are a significant part of this community and the impact of religion advocating for healthy life style as well as an emphasis on the role of god and prayer in predicting one's health were clearly identified. Our findings are consistent with other studies that have reported on these views of religion, and modesty in regards to cervical cancer screening [18, 20, 21]. At the system level, our study participants indicated that the health care providers who do not share their similar religious beliefs find it hard to understand why the women decline to screen.…”
Section: Discussionsupporting
confidence: 89%
“…Studies that have addressed cancer-screening barriers in Somali women indicated that some of the perceived barriers were fear of cancer, embarrassment of the screening test, and limited English ability [2426]; these barriers are similar to those reported by Somali men in this study. In addition to these perceived barriers, Somali men in our study stressed the fear of private health information being compromised by Somali interpreters; interpreters who are also members of their community.…”
Section: Discussionsupporting
confidence: 73%
“…To our knowledge this is the first study that has discussed at length the barriers faced by Somali men in relation to use and access to cancer screening services. Several studies have addressed cancer screening barriers for Somali women [2429]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations